Crude toxin of Aggregatibacter actinomycetemcomitans serotype-B increase PARP-1 expression in gingival epithelium - Ernie Maduratna Setiawatie (Universitas Airlangga, 2012)
Background: Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitants) serotype-B has long been associated with aggressive periodontitis. Gingival epithelial cell is exquisitely sensitive to the toxin so that may lead to disruption of the epithelial protective barrier, facilitating invasion and perturbation of the underlying connective tissue. Currently suggested that Aa serotypeB produce protein toxin that caused DNA strand breaks. PARP-1 is an abundant nuclear protein functioning as a DNA nick-sensor enzyme. PARP-1 was one of the first identified substrates of caspases, the main executioners of apoptosis. Therefore, a role for PARP-1 in the regulation of apoptosis has been suggested. Purpose: The purpose of this study was to prove PARP-1 expression in gingival epithelium caused by toxin exposure of A. actinomycetemcomitant serotype-B. Methods: This is an experimental study involving twenty adult mice strain Swiss Webster (balb C) divided randomly into two groups: control group (Group A) and toxin group (Group B). Both group were acclimated for one week before treatment. Group A was applied topically with sterile distillated water every 12 hours. Group B was applied topically by 100μg/ml of crude toxin A. actinomycetemcomitant serotype B at the buccal area of mandibular anterior teeth using Hamilton syringe. The mice were sacrificed at 24 hours after toxin application, and then the tissue sections of gingival epithelium were stained with immunohistochemistry to reveal the PARP-1 expression. The data were analyzed with t-test. Results: The PARP-1 expression exhibited an increase with the toxin group (mean= 48.9; SD= 2.01) compared with the control group (mean= 25.21; SD= 1.72). DNA fragmentation appeared from the agarose gel examination, marked as DNA laddering, indicate the cell apoptosis. Conclusion: In conclusion the crude toxin exposure of A. actinomycetemcomitant serotype-B leads to DNA fragmentation and increase PARP-1 expression. Latar belakang: Aggregatibacteractinomycetemcomitans (A. actinomycetemcomitant) serotype-B merupakan etiologi utama periodontitis agresif.